A Multicentric European Clinical Study on Custom-Made Porous Hydroxyapatite Cranioplasty in a Pediatric Population - Zaed, Ismail; Safa, Adrian; Spennato, Piero; Mottolese, Carmine; Chibbaro, Salvatore; Cannizzaro, Delia; Faggin, Roberto; Frassanito, Paolo; Maduri, Rodolfo; Messerer, Mahmoud; Servadei, Franco (Frontiers in Surgery, 2022)
Background: Cranioplasty (CP) is a surgical intervention aiming to re-establish the integrity of skull defects. Autologous bone and different heterologous materials are used for this purpose, with various reported related complications, especially in children. The aim of this study is to evaluate the complication rate in a multicentric cohort of pediatric patients treated with porous hydroxyapatite (PHA) CP implantation and to assess the reliability of post-marketing clinical data collected by the Manufacturing company. Methods: Authors proactively collected clinical data from 20 institutions in different European countries for patients under the age of 16 treated with PHA implant. Data were obtained through an on-site interview with the physicians in charge of the patients (Post-Marketing Surveillance, PMS group). The endpoints were the incidence of adverse events and of related implant removal. Clinical data were compared to the company-based register including all patients under the age of 16 who received the same implant from January 1, 2004, to December 31, 2020 and collecting complications reported by surgeons on a voluntary basis (Database, DB group). Results: The two groups were similar in terms of demographic characteristics and rate of complications. In PMS group, a total of 11 (16.9%) complications have been reported in the group of 65 patients proactively collected. Fractures and infections were both the most common complications with 4 cases each (6.2%). Both in case of infections and fractures, revision surgery was required for only one patient (1.5%). Three cases of displacements (4.5%) have been reported; in one case surgical revision was required (1.5%), for a total of 3 (4.5%) cases requiring surgical revision. The average follow-up was 26.7 months. Conclusions: Differently from a previous study in adult age, Pediatric Neurosurgeons are more prone to report even to the Manifacturing Company complications related to skull reconstruction in children. Therefore these data can be compared with other clinical studies. PHA cranioplasty in this series of 65 patients present a complication rate collected on-site similar to other heterologous material